Konservasi Tanaman Obat Sebagai Pusat Edukasi Dan Bisnis Berbasis Masyarakat Di Desa Waluran - Firhan Nurfaizi; Jujun Ratnasari; Vira Safitri Aulia; Teti Damayanti; Ruddy Indra Frahasta; Wiska Hera; Rima Ahadiah; Ulfa Fauzi; Meyssa Dwi; Sri Purnawati; Selpi Susilawati; M Zakaria; Rita Arlitia; Wilda Waliam; Rahmah, Laila (Universitas Muhammadiyah Malang, 2023)
Purpose - Many people do not know the potential that the Waluran Village area has. So, this service aims to provide education to the public regarding the potential of family medicinal plants (TOGA) through the conservation of medicinal plants. Design/methodology/approach - The service methods used are socialization, education, formation of medicinal plant conservation groups, and training. Finding - The results of the service showed that 50 types of medicinal plants were obtained from the exploration of medicinal plants, with the superior local plant in the target village being the leaves of karas bone (Chlorantus elatior). Originality/value - The local community also responded well, that this activity really helped the problems that occurred in their area.